Analisis Ekstrak Metanol Daun Sirsak (Annona Muricata Linn.) Terhadap Sel Kanker Prostat - Tiara Nabila Putri; Ardi Mustakim (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
Soursop leaves contain active compounds annonaceous acetogenins which are known to have cytotoxic activity against cancer cells. This study aims to evaluate the effect of soursop leaf methanol extract (EMDS) on the viability and growth inhibition of PC3 prostate cancer cells. The research method used was an in vitro experiment with subjects in the form of PC3 cell lines divided into five groups, namely the cell control group, the treatment group with EMDS at concentrations of 6.25; 12.5; and 25 mg/mL, and the group given doxorubicin as a positive control. Cell viability was analyzed using the MTT assay method after incubation for 0 and 24 hours, and cell morphology was observed. Data analysis was carried out using the ANOVA test. The results showed that the EMDS group with concentrations of 6.25 and 12.5 µg/mL experienced a decrease in OD values, although statistically there was no significant difference. The concentration of 12.5 µg/mL had the highest inhibitory effect on cell viability with an OD value of 0.94. Observation of cell morphology indicates the presence of cytotoxic effects. Conclusion: methanol extract of soursop leaves has potential as an anticancer agent against PC3 prostate cancer cells, although the inhibitory effect is relatively small.